2006
DOI: 10.1007/s10459-006-9039-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the influence of emotions and reflection upon multi-source feedback acceptance and use

Abstract: Negative feedback can evoke negative feelings and interfere with its acceptance. To overcome this, helpful interventions may include raising awareness of the influence of emotions, assisting recipients to focus their feedback on performance tasks, and providing facilitated reflection on feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
237
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(246 citation statements)
references
References 19 publications
6
237
2
1
Order By: Relevance
“…[9][10][11][12][13] It has also been suggested that if feedback elicits a negative response in doctors, it may be detrimental to their future performance. 8,[15][16][17] The current research highlights a mismatch between the conventional demonstration of the 'objectivity' of a survey tool, and the doubts and questions raised by those receiving the data, which prevented wholesale acceptance of its results. As rigorous pilot testing alone did not automatically translate into the results being trusted enough to be acted upon, the ability of the survey to bring about positive change seemed likely to be limited.…”
Section: Comparison With Existing Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…[9][10][11][12][13] It has also been suggested that if feedback elicits a negative response in doctors, it may be detrimental to their future performance. 8,[15][16][17] The current research highlights a mismatch between the conventional demonstration of the 'objectivity' of a survey tool, and the doubts and questions raised by those receiving the data, which prevented wholesale acceptance of its results. As rigorous pilot testing alone did not automatically translate into the results being trusted enough to be acted upon, the ability of the survey to bring about positive change seemed likely to be limited.…”
Section: Comparison With Existing Literaturementioning
confidence: 94%
“…14 Feedback that lacks credibility, that contradicts prior knowledge, or that is experienced as a threat at the individual level, is unlikely to be effective. 8,[15][16][17] This study was designed to capture the responses of GPs, practice nurses, and practice managers to patient feedback, using the national GP Patient Survey (www.gp-patient.co.uk/info/) as an example.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is evidence that unfacilitated feedback can cause negative emotional reactions, like denial and defensiveness, which can even raise barriers to reflection (DeNisi & Kluger 2000;Sargeant et al 2008;Overeem et al 2009) and behavioural change (Sargeant et al 2008). This problem can be overcome by facilitating feedback (Sargeant et al 2008) so as to stimulate feedback recipients to engage in constructive reflection on their practice (DeNisi & Kluger 2000;Smither et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is evidence that unfacilitated feedback can cause negative emotional reactions, like denial and defensiveness, which can even raise barriers to reflection (DeNisi & Kluger 2000;Sargeant et al 2008;Overeem et al 2009) and behavioural change (Sargeant et al 2008). This problem can be overcome by facilitating feedback (Sargeant et al 2008) so as to stimulate feedback recipients to engage in constructive reflection on their practice (DeNisi & Kluger 2000;Smither et al 2005). Self-assessment and peer meetings are ways to facilitate feedback (Ross & Bruce 2007;Tigelaar et al 2008) and several authors have highlighted their importance in facilitating teachers' professional growth (Ross & Bruce 2007;Tigelaar et al 2008;Mcleod & Steinert 2009;Schaub-de Jong et al 2009;Stalmeijer et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some educators suggest that receiving feedback mindfully contributes to learning, and extensive literature shows that such assessment can, with certain caveats, be practical, valid, and reliable. 8,9 The peer-assessment tool (mini-PAT), which evolved from multisource feedback and collates the views of various healthcare professionals with the aim of facilitating personal development, offers a more well-rounded overview than is possible when only 1 source provides feedback. [10][11][12] First introduced for physicians in the early 1990s, mini-PAT was designed to provide trainees anonymous feedback from peers and colleagues.…”
Section: Introductionmentioning
confidence: 99%